The association of multimorbidity and disability in a community-based sample of elderly aged 80 or older in Shanghai, China. Issue 1 (December 2016) - Su, Peng; Ding, Hansheng; Zhang, Wei; Duan, Guangfeng; Yang, Yitong; Chen, Rong; Duan, Zengjie; Du, Lixia; Xie, Chunyan; Jin, Chunlin; Hu, Chaoqun; Sun, Zixue; et al.
Abstract Background Both multimorbidity and activities of daily living (ADL) disability and instrument activities of daily living (IADL) disability are common among elderly individuals. ADL/IADL disability may reduce individuals' capacities for independent living and quality of life. This study aimed to examine the association between multimorbidity and ADL/IADL disability. Methods A multi-stage cluster sample of 2058 residents aged 80 or older was investigated in Shanghai, China. Multimorbidity was defined as the simultaneous presence of two or more chronic diseases with ten common chronic conditions under consideration. Subjects who responded that they "need partial or full assistance" to any ADL/IADL items were defined as having ADL/IADL disability. We examined the association of multimorbidity with ADL/IADL disability, adjusted for socio-demographic characteristics by using logistic regression. Results Of respondents, 23.23 % had ADL disability, 37.90 % had IADL disability, and 49.17 % had multimorbidity. After adjusted socio-demographic characteristics, a graded association was showed between ADL disability and the quantity of chronic conditions: odds ratio (OR) for 1 condition, 1.53(95 % confidence interval [CI], 1.04-2.24); OR for 2 conditions, 2.06(95 % CI, 1.43-2.96); OR for 3 conditions, 3.23(95 % CI, 2.14-4.86); OR for 4 or more conditions, 5.61(95 % CI, 3.26-9.66). Similar associations were also observed between the quantity of chronic conditions and IADL disability. Conclusions The quantity of chronic conditions had relatively strong association with both ADL and IADL disability. Initiating prevention of additional chronic conditions and interventions on clusters of diseases may decrease the potential risk of ADL/IADL disability. Additionally, more attention should been given to the older low-income women living with relatives/non-relatives with multimorbidity.